2015
DOI: 10.1016/j.celrep.2015.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Companion Blood Cells Control Ovarian Stem Cell Niche Microenvironment and Homeostasis

Abstract: The extracellular matrix plays an essential role for stem cell differentiation and niche homeostasis. Yet, the origin and mechanism of assembly of the stem cell niche microenvironment remain poorly characterized. Here, we uncover an association between the niche and blood cells, leading to the formation of the Drosophila ovarian germline stem cell niche basement membrane. We identify a distinct pool of plasmatocytes tightly associated with the developing ovaries from larval stages onward. Expressing tagged col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
82
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(84 citation statements)
references
References 55 publications
2
82
0
Order By: Relevance
“…This suggests that at least some, if not all, plasmatocytes have lineage-restricted progenitor capacity, underscoring further parallels with vertebrate EMPs [31]. Several studies have reported distinct subpopulations of plasmatocytes with varying combinations [37, 38], and quantitative expression differences [17], of commonly used plasmatocyte “markers” such as Hemolectin [39], Peroxidasin [40], P1 (Nimrod C1) [41], Croquemort [42], Eater [43], and the pan-hemocyte marker Hemese [44]. This favors the idea that specialized subsets of plasmatocytes exist, which could reflect distinct functional capabilities of these cells.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations
“…This suggests that at least some, if not all, plasmatocytes have lineage-restricted progenitor capacity, underscoring further parallels with vertebrate EMPs [31]. Several studies have reported distinct subpopulations of plasmatocytes with varying combinations [37, 38], and quantitative expression differences [17], of commonly used plasmatocyte “markers” such as Hemolectin [39], Peroxidasin [40], P1 (Nimrod C1) [41], Croquemort [42], Eater [43], and the pan-hemocyte marker Hemese [44]. This favors the idea that specialized subsets of plasmatocytes exist, which could reflect distinct functional capabilities of these cells.…”
Section: Introductionmentioning
confidence: 92%
“…From this point onward, the two blood cell lineages intermix, and distinguishing embryonic and Lymph Gland hemocytes is, according to current methodology, only possible by lineage tracing. In the adult, plasmatocytes reside in or close to a number of tissues, including fat body (which regulates metabolism and immunity), heart, respiratory (tracheal) system, gut, peripheral nervous system, and ovaries ([38, 9196] and Brückner lab in preparation). In addition, small numbers of crystal cells, but no lamellocytes, are present in the adult [2, 92, 97].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Virant et al indicated that there is a potential connection between the VSELs and the germinal system as well as the hemapoiesis reconstruction process [59]. Veronique et al [60] found that the “companion” blood cells are essential for the formation and the steady state of the ovarian germ stem cell nests. Therefore, we can conclude that the circulatory system is important for promoting ovarian functions.…”
Section: Factors Related To Ovarian Stem Cell Nests Agingmentioning
confidence: 99%